Riesgos, subjetividades y demandas de seguridad reflexiones para la investigación de demandas de seguridad - Celina Calzado, Mercedes; Lobo, Ana Laura (Nómadas. Critical Journal of Social and Juridical Science, 2009)
In an era characterized by risk aversion, the sense of uncertainty and the security crisis, this article addresses the link between the construction of security as a social problem, the public demands and the features that the state criminal justice policy assumes. Its contribution lies in analyzing the cultural factors involved in shaping perceptions of risk and new subjectivities and, to bring theoretical tools that will enable their approach. In particular, the article examines and deconstructs the key factors that constitute communities of victims as a body with common interests and, the relationship they establish with the criminal policy, directing the reflection towards the current democratic order.
Keywords: Risk; Victims; Security; Subjectivity; Community